Tindak Pidana Pencurian Menurut Perma Nomor 2 Tahun 2012 Dalam Perspektif Hukum Islam - ariman ariman; Maswandi Maswandi (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Theft is a crime that gets serious attention in Indonesian criminal law and Islamic law. This study aims to analyze the application of the Supreme Court Regulation (PERMA) No. 2 of 2012 related to the limitation of misdemeanors in cases of theft and reviewing it from the perspective of Islamic criminal law. Using normative research methods with the approach of legislation and conceptual, this study found that PERMA No. 2 of 2012 which raised the limit value of minor theft losses to Rp2, 500, 000 has an impact on changes in law enforcement patterns, including increased settlement of cases through tipiring and restorative justice mechanisms. However, this rule also poses a dilemma because it has the potential to increase the number of petty thefts, especially in Plantation and livestock areas. Meanwhile, Islamic criminal law does not recognize the category of petty theft and emphasizes the absolute protection of property rights through hudud sanctions in the form of cutting hands, with certain exceptions that consider emergencies. This study concludes that both legal systems emphasize justice, but have different bases and orientations in looking at the value of losses, social impacts, and the condition of the perpetrator.